Assessment of calpain and caspase systems activities during ageing of two bovine muscles by degradation patterns of αII spectrin and PARP‐1. (21st December 2015) - Saccà, Elena; Pizzutti, Nicoletta; Corazzin, Mirco; Lippe, Giovanna; Piasentier, Edi
Abstract: The activities of calpain and caspase systems during ageing in Longissimus lumborum (LL) and Infraspinatus (IS) muscles of Italian Simmental young bulls ( Bos taurus ) were assessed. Samples from 10 animals were collected within 20 min of exsanguination (T0), after 48 h (T1) and 7 days (T2) post mortem . Calpain and caspase activity were evaluated based on the formation of αII spectrin cleavage products of 145 kDa (SBDP145) and 120 kDa (SBDP120), respectively. Caspase activity was also assessed by the presence of poly (adenosine diphosphate‐ribose) polymerase‐1 (PARP‐1) cleavage product. At T0, LL showed higher levels of SBDP145 than IS ( P  < 0.01), while SBDP120 and PARP‐1 degradation products were similar between muscles. At T1, no difference was found in the level of SBDP145 between muscles, while SBDP120 and PARP‐1 cleavage products were not detected. At T2 neither αII spectrin nor PARP‐1 cleavage products were found. LL and IS showed different proteolysis after slaughter that was influenced more by calpain than caspase activity, which was detectable only in the early post mortem period.